2018
DOI: 10.1029/2018jb015641
|View full text |Cite
|
Sign up to set email alerts
|

Tongji‐Grace02s and Tongji‐Grace02k: High‐Precision Static GRACE‐Only Global Earth's Gravity Field Models Derived by Refined Data Processing Strategies

Abstract: In order to derive high‐precision static Gravity Recovery and Climate Experiment (GRACE)‐only gravity field solutions, the following strategies were implemented in this study: (1) a refined accelerometer calibration model that treats monthly accelerometer scales as a third‐order polynomial and daily accelerometer biases as a fifth‐order polynomial was developed to calibrate accelerometer measurements; (2) the errors of the acceleration and attitude data were estimated together with the geopotential coefficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 38 publications
(70 reference statements)
0
38
0
Order By: Relevance
“…In physical sense, the spatial distributions of stripes to some extent are related to the GRACE orbit configuration. As explained in previous studies (e.g., Chen et al, Dobslaw et al, ), the large orbit inclination (about 89°) for GRACE satellites leads to oversampling in the polar areas and sparser ground track coverage over medium and low latitude areas. As a consequence, much more striping errors over the medium‐ and low‐latitude areas exist in all the models in contrast to over the polar areas.…”
Section: Noise Analyses Of Monthly Gravity Field Solutionsmentioning
confidence: 77%
See 3 more Smart Citations
“…In physical sense, the spatial distributions of stripes to some extent are related to the GRACE orbit configuration. As explained in previous studies (e.g., Chen et al, Dobslaw et al, ), the large orbit inclination (about 89°) for GRACE satellites leads to oversampling in the polar areas and sparser ground track coverage over medium and low latitude areas. As a consequence, much more striping errors over the medium‐ and low‐latitude areas exist in all the models in contrast to over the polar areas.…”
Section: Noise Analyses Of Monthly Gravity Field Solutionsmentioning
confidence: 77%
“…Chen et al () showed that accurately modeling the time‐related variations in accelerometer parameters can lead to improvements on gravity field models. Here we present the statistics (mean values and standard deviations) of the estimated accelerometer scales and biases for the period April 2002 to August 2016 in Figure .…”
Section: Development Of Tongji‐grace2018 Monthly Solutionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Along with the KBR, other important sensors onboard GRACE satellites include Global Positioning System (GPS) receivers for precise orbit determination (POD), high-precision accelerometers for measuring non-gravitational forces and star cameras for attitude determination [4][5][6]. Based on the precise data collected by the above sensors, many scientific institutions have produced high-quality static and temporal gravity field models [7][8][9][10][11], which are successfully adopted for quantitative researches concerning the Earth's mass changes, such as global mean sea-level variations [12,13], continental water balance [14,15], and the Tibetan Plateau and Antarctic regional ice losses [16,17].…”
Section: Introductionmentioning
confidence: 99%